Effects of dry needling on spasticity, cortical excitability, and range of motion in a patient with multiple sclerosis: a case report - Haniyeh Choobsaz; Nastaran Ghotbi; Noureddin Nakhostin Ansari (Journal of Medical Case Reports, 2024)
Abstract Background Dry needling is an intervention used by physiotherapists to manage muscle spasticity. We report the effects of three sessions of dry needling on ankle plantar flexor muscle spasticity and cortical excitability in a patient with multiple sclerosis. Case presentation The patient was a 40-year-old Iranian woman with an 11-year history of multiple sclerosis. The study outcomes were measured by the modified modified Ashworth scale, transcranial magnetic stimulation parameters, and active and passive ankle range of motion. They were assessed before (T0), after three sessions of dry needling (T1), and at 2-week follow-up (T2). Our result showed: the modified modified Ashworth scale was improved at T2 from, 2 to 1. The resting motor threshold decreased from 63 to 61 and 57 at T1 and T2, respectively. The single test motor evokes potential increased from 76.2 to 78.3. The short intracortical inhibition increased from 23.6 to 35.4 at T2. The intracortical facilitation increased from 52 to 76 at T2. The ankle active and passive dorsiflexion ROM increased ~ 10° and ~ 6° at T2, respectively. Conclusion This case study presented a patient with multiple sclerosis who underwent dry needling of ankle plantar flexors with severe spasticity, and highlighted the successful use of dry needling in the management of spasticity, ankle dorsiflexion, and cortical excitability. Further rigorous investigations are warranted, employing randomized controlled trials with a sufficient sample of patients with multiple sclerosis. Trial registration IRCT20230206057343N1, registered 9 February 2023, https://en.irct.ir/trial/68454